Resistive index and peak systolic velocity for congenital talipes equinovarus: A color Doppler ultrasonography study - Bozkurt, Celal (Jt Dis Relat Surg, 2020)
OBJECTIVES: This study aims to investigate whether resistive index (RI) and peak systolic velocity (PSV) are suitable parameters to determine if a clubfoot differs from feet of the normal population. PATIENTS AND METHODS: Fifty-four feet of 27 clubfoot patients (22 males, 5 females; mean age 30.4±16.3 months; range, 5 to 72 months) were included in this retrospective study conducted between December 2017 and January 2019. Twenty-seven feet were conservatively treated, 19 had surgical treatment, and eight feet were healthy in patients with unilateral clubfoot. In addition, 22 feet of 11 normal controls (6 males, 5 females; mean age 33.4±15.3 months; range, 15 to 60 months) were studied. Color Doppler ultrasonography examinations were performed to evaluate the three major arteries of the leg and foot: dorsalis pedis (dp), tibialis posterior (tp), and popliteal (pop). Color filling, flow direction, spectral analysis, velocity, and RI were examined. RESULTS: With the exception of the dp artery RI, the PSV and RI values for all arteries differed significantly from those of the control group. There were no significant differences among the conservative, surgical, and healthy groups, while there were significant differences between each of the treated groups and the control group. Tibialis posterior artery PSV and pop artery RI were the best parameters to identify clubfoot and the cut-off points were 54 cm/second and 0.77, respectively. CONCLUSION: Peak systolic velocity and RI may be accepted as important parameters for identification of clubfoot deformity. Tibialis posteriorartery PSV and pop artery RI are the best- detailed parameters for this examination.